2007
DOI: 10.1007/s00414-007-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of sterilisation techniques on subsequent DNA profiling

Abstract: It is important that contamination from extraneous DNA should be minimised on items used at crime scenes and when dealing with exhibits within the laboratory. Four sterilisation techniques (UV, gamma and beta radiation and ethylene oxide treatment) were examined for their potential to degrade contaminating DNA to such an extent that subsequent DNA profiling was impossible. This work indicated that the most successful technique to reduce DNA contamination was ethylene oxide treatment. Of the radiation technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…These include the practices to minimize laboratory-induced contamination. Recommendations for contamination prevention in laboratory controlled environments include pressurized facilities, appropriate laboratory gear, the analysis of a single sample at a time, DNA-free consumables, and decontamination practices (eg, exposure to UV light and/or ethylene oxide) (29). Unfortunately, similar constraints have not made their way into the protocols for evidence collection and handling (16,20), Proper contamination prevention prac-tices need to be implemented not only in the laboratory but also at the crime scene.…”
Section: Laboratory Practicesmentioning
confidence: 99%
“…These include the practices to minimize laboratory-induced contamination. Recommendations for contamination prevention in laboratory controlled environments include pressurized facilities, appropriate laboratory gear, the analysis of a single sample at a time, DNA-free consumables, and decontamination practices (eg, exposure to UV light and/or ethylene oxide) (29). Unfortunately, similar constraints have not made their way into the protocols for evidence collection and handling (16,20), Proper contamination prevention prac-tices need to be implemented not only in the laboratory but also at the crime scene.…”
Section: Laboratory Practicesmentioning
confidence: 99%
“…Efforts to minimize the occurrence of exogenous DNA in samples include specific quality control procedures designed to prevent laboratory based contamination (21,22), treatment of consumables to remove DNA (23,24), and the selection of reagents shown to be as free of exogenous DNA as possible. For example, during the manufacturer's validation ofthe iD kit no non-specific peaks were generated (13).…”
mentioning
confidence: 99%
“…13 Further investigations revealed that not all conventional irradiation techniques resulted in the complete removal of amplifiable DNA in manufacturing sterilisation processes. 14,15 Due to errors at the manufacturing stage, the latent threats were so deeply embedded into the system that practitioners and investigators could not predict or detect the errors until multiple adverse events had occurred. Concepts such as TEM and situational awareness have up until now been foreign to the majority of those practising in the area of sexual assault.…”
Section: Investigative Stagementioning
confidence: 99%